Unleashing a novel function of Endonuclease G in mitochondrial genome instability - Dahal, Sumedha; Siddiqua, Humaira; Sharma, Shivangi; Babu, Ravi K; Rathore, Diksha; Sharma, Sheetal; Raghavan, Sathees C (eLife, 2022)
Having its genome makes the mitochondrion a unique and semiautonomous organelle within cells. Mammalian mitochondrial DNA (mtDNA) is a double-stranded closed circular molecule of about 16 kb coding for 37 genes. Mutations, including deletions in the mitochondrial genome, can culminate in different human diseases. Mapping the deletion junctions suggests that the breakpoints are generally seen at hotspots. ‘9 bp deletion’ (8271–8281), seen in the intergenic region of cytochrome c oxidase II/tRNALys, is the most common mitochondrial deletion. While it is associated with several diseases like myopathy, dystonia, and hepatocellular carcinoma, it has also been used as an evolutionary marker. However, the mechanism responsible for its fragility is unclear. In the current study, we show that Endonuclease G, a mitochondrial nuclease responsible for nonspecific cleavage of nuclear DNA during apoptosis, can induce breaks at sequences associated with ‘9 bp deletion’ when it is present on a plasmid or in the mitochondrial genome. Through a series of in vitro and intracellular studies, we show that Endonuclease G binds to G-quadruplex structures formed at the hotspot and induces DNA breaks. Therefore, we uncover a new role for Endonuclease G in generating mtDNA deletions, which depends on the formation of G4 DNA within the mitochondrial genome. In summary, we identify a novel property of Endonuclease G, besides its role in apoptosis and the recently described ‘elimination of paternal mitochondria during fertilisation.
Keywords: tetraplexes; mitochondrial fragility; Endo G; double-strand breaks; MMEJ; mitochondrial deletion; G4 DNA